Management of Posterior Cruciate Ligament Tibial Avulsion Injuries: A Systematic Review. Issue 3 (March 2018) - Hooper, Perry O.; Silko, Chris; Malcolm, Tennison L.; Farrow, Lutul D.
Background: Tibial-sided avulsion injuries of the posterior cruciate ligament (PCL) generally require surgical intervention. No consensus exists concerning the optimal surgical treatment approach for these injuries. Purpose: To perform a systematic review investigating the open and arthroscopic surgical treatment modalities, outcomes, and complications of PCL tibial-sided bony avulsions. Study Design: Systematic review; Level of evidence, 4. Methods: The authors performed a systematic review of the literature utilizing PubMed and EMBASE from 1975 to present outlining open versus arthroscopic surgical repair of PCL bony avulsion injuries and comparing subjective and objective postoperative patient-reported outcomes, including Tegner, IKDC (International Knee Documentation Committee), and Lysholm scoring systems, as well as rates of patient complications. The quest was performed in June 2016, and searched terms included posterior cruciate ligament, PCL, bony, avulsion(s), tibial-sided, open, and arthroscopic . Inclusion criteria included English-language studies involving surgical fixation strategies for PCL tibial-sided bony avulsions. Exclusion criteria included non-English language, case studies/case series, and subject matter not pertaining to PCL bony avulsions. Results: Twenty-eight articles comprising 637 patients met the criteria and were included in the final review. PCL injuries with a tibial-sided avulsion were the result of motor vehicle accidents in 68.4% of patients, with 59.0% of these injuries resulting from motorcycle accidents. The arthroscopic group had better IKDC grade A scores (78.9%), indicating a normal knee postoperatively, as compared with the open group (65.9%). The postoperative Lysholm scores were similar between the groups, with a mean of 95.0 in the arthroscopic group and 92.8 in the open group. The arthroscopic group also reported 100% return to preinjury level of activity, compared with 86.2% in the open group. The most common complication in both groups was arthrofibrosis, which was reported more often in the arthroscopic group (0%-35%) versus the open treatment group (0%-25%). Conclusion: In patients with displaced tibial-sided PCL avulsion fractures treated operatively, surgical approaches render similar outcomes and risks. While the arthroscopic group had somewhat higher subjective and objective knee outcome scores, it demonstrated a slightly higher rate of arthrofibrosis. The clear advantage of the arthroscopic approach is that concomitant intra-articular injuries seen on preoperative magnetic resonance imaging, such as meniscal tears or osteochondral loose fragments, can be addressed at the time of the index operation.